THE LIS STUDY (LYUBERTSY STUDY ON MORTALITY RATE IN PATIENTS AFTER ACUTE MYOCARDIAL INFARCTION). EVALUATION OF DRUG THERAPY. PART 2. INFLUENCE OF PREVIOUS DRUG TREATMENT ON LONG-TERM LIFE PROGNOSIS - S. Yu. Martsevich; M. L. Gynzburg; N. P. Kutishenko; A. D. Deev; V. P. Smirnov; L. U. Drozdova; E. V. Daniels; A. V. Fokina (Столичная издательская компания, 2015)
Aim. To evaluate drug therapy received by patients who had survived acute myocardial infarction (AMI) in the framework of the AMI register (the "LIS" study) and estimate this therapy influence on long-term outcomes of the disease. Material and methods. The total of 961 patients of 1133 enrolled in the "LIS" study , were discharged from hospital. 191 patients had died during follow-up. 632 patients (who had survived and consented to visit out-patient clinic) underwent repeated examination (median of follow-up 1.6 [1.0; 2.4] years). Data about treatment before and during AMI were received from patient's charts; data about treatment after AMI were obtained from out-patient medical records. Results. Before reference AMI only a small number of the patients received the main drug groups (antiplatelet agents, β-blockers, ACE inhibitors, statins), at that ACE inhibitors were prescribed more often than the others. Use of β-blockers and ACE inhibitors before reference AMI significantly improved long-term life prognosis [relative risk (RR) 0.70 and 0.66, respectively]. Rate of the main drug groups prescribed in hospital was rather high with the exception of thrombolytics (less than 10%). Thrombolytics, β-blockers and antiplatelet agents prescribed in hospital significantly improved long-term life prognosis of patients (RR 0.42, 0.65 and 0.58 respectively). At the second visit (according to data of out-patient medical records) rate of antiplatelet agents, ACE inhibitors, β-blockers and statins prescription exceeded 60%. Conclusion. Very low prevalence of adequate drug therapy preceding AMI determines high mortality rate among survived acute stage of myocardial infarction patients in long-term period.